Handschriftliche Sprachproduktion : sprachstrukturelle und ontogenetische Aspekte - Nottbusch, Guido (Linguistische Arbeiten (Max Niemeyer Verlag), 2008)
While writing a word, everybody will have paused for a moment to think about the correct spelling. It is just this behaviour which the present book studies using modern technology. As schoolchildren were writing, the position of their pens was recorded 100 times per second. By checking where and in which words hesitations and possibly errors occurred, it was possible to determine the level of the children?s orthographic knowledge? conscious and unconscious.